Tecnologia para texturização hemisférica suave de células solares fotovoltaicas - Fernanda Pelegrini Honorato (2007)
The use of Silicon solar cells has been increasing in the last decades. This alternative form of energy acquires more market space as device efficiency increases. At Fundação Centro Tecnológico de Minas Gerais - CETEC-MG, where part of this research was developed, Silicon is prepared to be used in solar cells from its purification to its deposition on the doped bulk. On this research, the bulk Silicon texturization to increase the exposed area to the Sun is used as a possibility to improve conversion efficiency of solar cells. Current methods to improve solar-cell efficiency through texturization rely on area gain and employ either a poorly controlled population of the surface with small pyramids (hillocks) or an anisotropic etching of the surface to yield an array of pyramidal pits, respectively. We propose to use a feature of the anisotropic etching of bulk Silicon, to texture the front cell surface with a contiguous array of smooth hemispherical cavities. The method is compatible with the fabrication process of Silicon solar cell and there is no need for a high-definition lithographic mask. This method offers an accurate control of the array parameters and only requires a single exposure mask and two etch steps with a Potassium Hydroxide (KOH) aqueous solution. The area gain and the reflectance reduction analysis prove the texturing capability to increase the conversion efficiency of solar cells. We compare a textured surface with a plane surface and analyze the profile of the textures. To obtain the p-n junction, it is used a kind of physical vapor deposition with Argon plasma assistance. This plasma is used to accelerate the deposition and to improve the deposited thin film. A Langmuir probe is used to obtain the plasma characteristics.